(3VeGf GdONd GdHOjd aj GdeedcI GdCQOfjI GdgGTejI Hjf GdfXQjI hGdJWHjb (B/s - (3GdeUQj, eMeO Qajbs ((3YeGf(B: s (3GdeDSSI GdCQOfjI ddJLgjRGJ GdecJHjI(B, s, 1992)
(3GdJCejf hGdJCejf Ydi GdMjGI(B-(3GdJShjb hGdEOGQI(B-(3GdfhGMj GdafjI hYbhO GdJCejf Ydi GdMjGI(B-(3GdJCejf Ydi GdMjGI hGdOhd GdfGejI(B-(3GdVeGf GdELJeGYjs
(3edMb U(B. 255s
Keywords: (3GdJCejf (B- (3GdHfhcs; (3GdJShjbs